The Association between Non-Medical Prescription Drug Use and Suicidal Behavior among United States Adolescents - Amanda L. Divin; Keith J. Zullig (AIMS Press, 2014)
Adolescence represents a vulnerable time for the development of both drug use/abuse and mental illness. Although previous research has substantiated a relationship between drug use and suicidal behavior, little research has examined this relationship with non-medical prescription drug use. Given the growing prevalence of non-medical prescription drug use (NMPDU) among adolescents, this study explored the association between NMPDU and suicidal behavior. Nationally representative data were derived from 16, 410 adolescents who completed the 2009 National Youth Risk Behavior Survey. Approximately 19.8% of participants reported lifetime NMPDU. NMPDU was associated with significantly increased odds of suicidal behavior (P < 0.01), with seriously considering attempting suicide and making a plan about attempting suicide representing the strongest correlates for males and females. Results suggest the importance of 1) continued reinforcement of drug education programs in high school begun at earlier ages and 2) mental health care and screenings among adolescents.